Preparation method and application of flexible ceramic fiber sponge and spinning solution
The preparation of flexible ceramic fiber sponge through the spinning solution of polyvinylpyrrolidone and polysilazane solves the problem of integration of flexibility and function in the prior art, and realizes the wave absorption and thermal insulation properties of efficient preparation of flexible ceramic materials, which are suitable for multifunctional material design.
Patent Information
- Application Number
- CN202510529585.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-01
AI Technical Summary
It is difficult to prepare flexible ceramic materials with wave absorption and heat insulation functions in the prior art, and the viscosity and surface tension of the spinning solution need to be highly matched with the airflow spinning process, and the selection of solvents and side reactions affect the purity of the ceramic.
A spinning solution with polyvinylpyrrolidone and polysilazane as precursors and trichloromethane and DMF as solvents was used to prepare flexible ceramic fiber sponges by airflow spinning, drying and pyrolysis, and optimize the composition and pyrolysis conditions of the spinning solution to achieve flexibility and functional integration.
A flexible ceramic fiber sponge has excellent wave absorption and heat insulation properties, suitable for multifunctional material design and easy to mass production.
Smart Images

Figure CN120401027A_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a preparation method, an application and a spinning solution of a flexible ceramic fiber sponge, belonging to the technical field of microwave absorbing materials. Background Art
[0002] Microwave absorbing materials are widely used in many fields such as military, communication, aerospace, and electronic equipment. Precursor-derived ceramics (PDCs) have excellent high-temperature stability, oxidation / corrosion resistance, and adjustable electrical / dielectric properties, and have developed into promising high-temperature microwave absorbing materials in the future. By means of fiberization, not only the microwave absorbing performance of the precursor ceramics themselves can be improved, but also their low density and high porosity characteristics can achieve excellent heat insulation effects and improve the intrinsic brittleness of the ceramics.
[0003] Chinese Patent CN106757529A discloses a preparation method of a flexible hydrophobic silicon carbide nanofiber cloth with electromagnetic wave absorption effect. It is prepared by combining electrospinning and polymer-derived ceramics. Polycarbosilane (PCS) is used as the precursor of silicon carbide, polyvinylpyrrolidone (PVP) is used as the spinning aid, and a mixed solvent of chloroform and dimethylformamide is used as the spinning solvent. The spun PCS / PVP nanofiber cloth is transformed into a SiC nanofiber cloth through thermal oxidative crosslinking curing and high-temperature heat treatment. Due to the network structure of the SiC nanofiber cloth and the excellent mechanical properties of single nanofibers, the SiC nanofiber cloth has good flexibility. At the same time, due to the presence of pores between fibers and the grooves on the fiber surface in the SiC nanofiber cloth, the SiC nanofiber cloth exhibits hydrophobicity.
[0004] The SiC nanofiber cloth obtained by high-temperature heat treatment in this patent is cut into a size of 4*4 cm and bent under different external forces, and the SiC nanofiber cloth is not damaged. The SiC nanofiber cloth of this patent has good absorption ability for high-frequency electromagnetic waves. However, the preparation method of this patent uses electrospinning and cannot be formed into blocks, so its application is limited.
[0005] Zhang Yuyu et al. published in "Journal of Inorganic Materials": Preparation and microwave absorbing properties of polymer-derived SiHfCN ceramics. Four kinds of nanoceramics, namely SiHfCN, SiHfCN-C, SiHfCN-B and SiHfCN-N, were obtained by single-source modification of polyazosilane combined with different compounds. The thickness of the SiHfCN sample is 3.40 mm and its RL min is only -13.8 dB. When the thickness of SiHfCN-C is 2.96 mm, R Lmin can reach -50.6 dB. When the thickness of SiHfCN-N is 2.55 mm, its RL min can reach -63.5 dB. When the thickness of SiHfCN-B is 2.73 mm, its RL minIt can reach -57.3 dB. However, the problem with this article is that the material is not a flexible material and cannot improve the problem of the intrinsic brittleness of ceramics.
[0006] Chinese Patent CN116623316A discloses a method for preparing a self-absorbing water sponge for electromagnetic wave absorption by high-speed air spinning. The selected material is a metal salt, which is used in the field of wave absorption and has high water absorption. However, metal salt materials decompose endothermically at high temperatures, reducing the surface temperature of the material and are usually used for flame retardancy. The thermal conductivity of a single metal salt is relatively high and it cannot directly reflect or block heat, so it cannot be used as a thermal insulation material. When air spinning is applied to precursor ceramics, there are many problems that need to be overcome: the viscosity and surface tension of the spinning solution of the ceramic precursor need to be highly matched with the air spinning process. Too low viscosity will cause fiber breakage, and too high viscosity will make it difficult to form a continuous jet; volatile solvents (such as tetrahydrofuran and xylene) also need to be used to promote rapid fiber curing, but such solvents may react with the precursor or leave residual impurities, affecting the purity of the subsequent pyrolyzed ceramics. Summary of the Invention
[0007] The present invention provides a method for preparing a flexible ceramic fiber sponge, its application, and a spinning solution. The flexible ceramic fiber sponge obtained by the preparation method can achieve the flexibility of ceramics and has the integrated functions of wave absorption and heat insulation.
[0008] In a first aspect, the present invention provides a spinning solution, which includes a solvent and a precursor. The precursor is: polyvinylpyrrolidone and polysilazane; the solvent is chloroform and DMF.
[0009] Further, the solvent is chloroform and DMF with a mass ratio of 1:3.
[0010] Further, the polyvinylpyrrolidone accounts for 7%-15% of the mass of the spinning solution.
[0011] Preferably, the polyvinylpyrrolidone accounts for 8%-12% of the mass of the spinning solution.
[0012] More preferably, the polyvinylpyrrolidone accounts for 9%-11% of the mass of the spinning solution.
[0013] Even more preferably, the polyvinylpyrrolidone accounts for 10%-11% of the mass of the spinning solution.
[0014] Further, the polysilazane accounts for 14%-30% of the mass of the spinning solution.
[0015] Preferably, the polysilazane accounts for 16%-24% of the mass of the spinning solution.
[0016] More preferably, the polysilazane accounts for 18%-22% of the mass of the spinning solution.
[0017] More preferably, the polysilazane accounts for 20%-22% of the mass of the spinning solution.
[0018] Furthermore, the spinning solution, by mass fraction, includes 7%-15% polyvinylpyrrolidone, 14%-30% polysilazane, and the balance being the solvent.
[0019] Furthermore, the mass ratio of the polyvinylpyrrolidone to the polysilazane is 1:(1-2).
[0020] Preferably, the mass ratio of the polyvinylpyrrolidone to the polysilazane is 1:2.
[0021] In a second aspect, the present invention provides a method for preparing a flexible ceramic fiber sponge, comprising the following steps:
[0022] (1) Obtaining a flexible fiber sponge by air-jet spinning the spinning solution;
[0023] (2) Drying the flexible fiber sponge obtained in step (1) to obtain a dried flexible fiber sponge;
[0024] (3) Pyrolyzing the dried flexible fiber sponge obtained in step (2) to obtain a flexible ceramic fiber sponge.
[0025] Furthermore, in step (1), the propulsion speed of the air-jet spinning is 0.01-0.03 ml / min, the collection distance is 20-35 cm, and the air pressure is 0.1 mpa-0.2 mpa.
[0026] Preferably, in step (1), the spinning is carried out using two 1-ml medical syringes simultaneously.
[0027] Preferably, the drying temperature in step (2) is 70-80°C.
[0028] Furthermore, the pyrolysis in step (3) is carried out under the protection of an inert gas.
[0029] Preferably, the inert gas includes but is not limited to argon, nitrogen, and helium.
[0030] More preferably, the inert gas is argon.
[0031] Furthermore, the pyrolysis temperature in step (3) is 1300-1500°C.
[0032] Preferably, the pyrolysis temperature is 1400-1500°C.
[0033] In a third aspect, the present invention provides a flexible ceramic fiber sponge prepared by the above preparation method.
[0034] Fourthly, the present invention provides an application of the flexible ceramic fiber sponge prepared by the above preparation method in the integrated design of multifunctional materials; the multifunction is: wave absorption and heat insulation.
[0035] Fifthly, the present invention provides a thermal protection / wave absorption device, including the flexible ceramic fiber sponge prepared by the above preparation method.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) By adjusting the dosage relationship of chloroform and DMF and the dosage relationship of PVP and polysilazane, the present invention realizes the flexibility of ceramics.
[0038] (2) By adjusting the dosage relationship of PVP and polysilazane and optimizing the pyrolysis conditions in the preparation method, the obtained flexible ceramic sponge has the integrated functions of wave absorption and heat insulation.
[0039] (3) The preparation method of the present invention is simple and efficient, and is easy to mass-produce. Description of the Drawings
[0040] Figure 1 The macroscopic morphology of the flexible ceramic sponge prepared in Example 1.
[0041] Figure 2 The stress-strain curves under different compression displacements
[0042] Figure 3 The microscopic morphology of the flexible ceramic sponge prepared in Example 1. Detailed Embodiments
[0043] In order to make the technical means, creative features, achieved purposes and functions of the present invention easy to understand, the following specific embodiments are used to further clarify the present invention. However, the following embodiments are only the preferred embodiments of the present invention, not all. Based on the embodiments in the implementation manners, other embodiments obtained by those skilled in the art without creative efforts all belong to the protection scope of the present invention. It is worth noting that the raw materials used in the present invention are all ordinary commercially available products, and no specific limitation is made on their sources. The technical and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the technical field to which the present invention belongs.
[0044] Unless otherwise specified, the concentrations / percentages mentioned in the present invention are all mass concentrations.
[0045] The present invention does not limit the sources of the raw materials used. Unless otherwise specified, the raw materials used in the present invention are all ordinary commercially available products in the technical field.
[0046] The polysilazane model of the present invention is Durazane 1800.
[0047] The molecular weight of PVP is 1,300,000.
[0048] 1. Examples and Comparative Examples
[0049] Example 1 A flexible ceramic fiber sponge
[0050] The raw material composition is: 10% PVP, 20% polysilazane and the balance of solvent, and the solvent is chloroform and DMF with a mass ratio of 1:3.
[0051] The method for preparing the flexible ceramic fiber block with wave absorbing and heat insulating functions comprises the following steps:
[0052] (1) Mix chloroform and DMF in a mass ratio of 1:3 and stir for 2 hours;
[0053] (2) adding 10% by mass of PVP and 20% by mass of polysilazane to the solvent obtained in step (1) and stirring for 5 hours to obtain a spinning solution;
[0054] (3) The spinning solvent obtained in step (2) was placed in a 1 ml medical needle tube and subjected to a spinning experiment at a propulsion speed of 0.03 ml / min, an air flow pressure of 0.1 MPa, and a collection distance of 35 cm to obtain a fiber block;
[0055] (4) drying the fiber block obtained in step (3) at a drying temperature of 80° C.
[0056] (5) The fiber block dried in step (4) is placed in a tube furnace and heated to 1400°C. The heating rate from room temperature to 350°C is 2°C / min, and the heating rate from 350°C to 1400°C is 1°C / min to obtain a flexible ceramic fiber sponge.
[0057] Example 2 A flexible ceramic fiber sponge
[0058] The method comprises the following raw materials: a mixed solvent of chloroform and DMF (mass ratio is 1:3), 11% PVP, and 22% polysilazane.
[0059] The method for preparing the flexible ceramic fiber block with wave absorbing and heat insulating functions comprises the following steps:
[0060] (1) Mix chloroform and DMF in a mass ratio of 1:3 and stir for 2 hours;
[0061] (2) adding 11% by mass of PVP and 22% by mass of polysilazane to the solvent obtained in step (1) and stirring for 5 hours to obtain a spinning solution;
[0062] (3) Put the spinning solvent obtained in step (2) into a 1-ml medical syringe for spinning experiments, with a pushing speed of 0.03 ml / min, an air flow pressure of 0.1 mpa, and a collection distance of 35 cm to obtain fiber blocks;
[0063] (4) Dry the fiber blocks obtained in step (3) at a drying temperature of 80 °C;
[0064] (5) Put the fiber blocks dried in step (4) into a tube furnace and heat up to 1500 °C, with a heating rate of 2 °C / min from room temperature to 350 °C and a heating rate of 1 °C / min from 350 °C to 1400 °C to obtain a flexible ceramic fiber sponge.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that the mass ratio of chloroform to DMF is different.
[0067] The raw material composition is: 10% PVP, 20% polysilazane, and the balance is the solvent. The solvent is chloroform and DMF with a mass ratio of 4:1.
[0068] The preparation method of the flexible ceramic fiber block with wave absorption and heat insulation functions includes the following steps:
[0069] (1) Mix chloroform and DMF with a mass ratio of 4:1 and stir for 2 hours;
[0070] (2) Add 10% PVP by mass fraction and 20% polysilazane by mass fraction to the solvent obtained in step (1) and stir for 5 hours to obtain a spinning solution;
[0071] (3) Put the spinning solvent obtained in step (2) into a 1-ml medical syringe for spinning experiments, with a pushing speed of 0.03 ml / min, an air flow pressure of 0.1 mpa, and a collection distance of 35 cm to obtain fiber blocks;
[0072] (4) Dry the fiber blocks obtained in step (3) at a drying temperature of 80 °C;
[0073] (5) Put the fiber blocks dried in step (4) into a tube furnace and heat up to 1400 °C, with a heating rate of 2 °C / min from room temperature to 350 °C and a heating rate of 1 °C / min from 350 °C to 1400 °C to obtain a flexible ceramic fiber sponge.
[0074] Comparative Example 2
[0075] The raw material composition is: 8% PVP, 22% polysilazane, and the balance is the solvent. The solvent is chloroform and DMF with a mass ratio of 1:3.
[0076] The preparation method of the flexible ceramic fiber block with wave absorption and heat insulation functions comprises the following steps:
[0077] (1) Mix trichloromethane and DMF with a mass ratio of 1:3 and stir for 2 hours;
[0078] (2) Add 8% by mass of PVP and 22% by mass of polysilazane to the solvent obtained in step (1) and stir for 5 hours to obtain a spinning solution;
[0079] (3) Put the spinning solvent obtained in step (2) into a 1 ml medical syringe to conduct a spinning experiment, wherein the pushing speed is 0.03 ml / min, the air flow pressure is 0.1 mpa, and the collection distance is 35 cm to obtain a fiber block;
[0080] (4) Dry the fiber block obtained in step (3), and the drying temperature is 80 °C;
[0081] (5) Put the fiber block dried in step (4) into a tube furnace and heat it up to 1400 °C. The heating rate from room temperature to 350 °C is 2 °C / min, and the heating rate from 350 °C to 1400 °C is 1 °C / min to obtain a flexible ceramic fiber sponge.
[0082] Comparative Example 3
[0083] The difference from Example 1 is that polysilazane is replaced by polycarbosilane.
[0084] The raw material composition is: 10% PVP, 20% polycarbosilane and the balance of the solvent. The solvent is trichloromethane and DMF with a mass ratio of 1:3.
[0085] The preparation method of the flexible ceramic fiber block with wave absorption and heat insulation functions comprises the following steps:
[0086] (1) Mix trichloromethane and DMF with a mass ratio of 1:3 and stir for 2 hours;
[0087] (2) Add 10% by mass of PVP and 20% by mass of polycarbosilane to the solvent obtained in step (1) and stir for 5 hours to obtain a spinning solution;
[0088] (3) Put the spinning solvent obtained in step (2) into a 1 ml medical syringe to conduct a spinning experiment, wherein the pushing speed is 0.03 ml / min, the air flow pressure is 0.1 mpa, and the collection distance is 35 cm to obtain a fiber block;
[0089] (4) Dry the fiber block obtained in step (3), and the drying temperature is 80 °C;
[0090] (5) Place the fiber block dried in step (4) into a tubular furnace and heat it to 1400 °C. The heating rate from room temperature to 350 °C is 2 °C / min, and the heating rate from 350 °C to 1400 °C is 1 °C / min to obtain a flexible ceramic fiber sponge.
[0091] Comparative Example 4
[0092] The difference from Example 1 lies in the different mass fractions of PVP and polysilazane.
[0093] The raw material composition is: 16% PVP, 32% polysilazane and the balance of the solvent. The solvent is a mixture of chloroform and DMF with a mass ratio of 1:3. It includes the following raw materials: a mixed solvent of chloroform and DMF (mass ratio of 1:3).
[0094] The preparation method of the flexible ceramic fiber block with wave absorption and heat insulation functions includes the following steps:
[0095] (1) Mix chloroform and DMF with a mass ratio of 1:3 and stir for 2 hours;
[0096] (2) Add 16% PVP by mass fraction and 32% polysilazane by mass fraction to the solvent obtained in step (1) and stir for 5 hours to obtain a spinning solution;
[0097] (3) Put the spinning solvent obtained in step (2) into a 1 ml medical syringe for a spinning experiment, with a propulsion speed of 0.03 ml / min, an air flow pressure of 0.1 mpa, and a collection distance of 35 cm.
[0098] However, during the spinning in step (3), it is difficult to stretch the spinning solution and it is difficult to obtain complete fibers.
[0099] Comparative Example 5
[0100] The difference from Example 1 lies in the different mass fractions of PVP and polysilazane.
[0101] The raw material composition is: 6% PVP, 12% polysilazane and the balance of the solvent. The solvent is a mixture of chloroform and DMF with a mass ratio of 1:3.
[0102] The preparation method of the flexible ceramic fiber block with wave absorption and heat insulation functions includes the following steps:
[0103] (1) Mix chloroform and DMF with a mass ratio of 1:3 and stir for 2 hours;
[0104] (2) Add 6% PVP by mass fraction and 12% polysilazane by mass fraction to the solvent obtained in step (1) and stir for 5 hours to obtain a spinning solution;
[0105] (3) Put the spinning solvent obtained in step (2) into a 1 ml medical syringe for the spinning experiment, with a pushing speed of 0.03 ml / min, an air flow pressure of 0.1 mpa, and a collection distance of 35 cm.
[0106] However, during the spinning in step (3), the spinning solution could not obtain a polymer jet, and it was difficult to obtain complete fibers.
[0107] Comparative Example 6
[0108] The difference from Example 1 is the solvent. Replace the solvent in Example 1 with acetonitrile, tetrahydrofuran, and DMF respectively, and keep the remaining conditions unchanged.
[0109] (1) Add 10% by mass of PVP and 20% by mass of polysilazane to the solvent and stir for 5 hours to obtain a spinning solution;
[0110] (2) Put the spinning solvent obtained in step (1) into a 1 ml medical syringe for the spinning experiment, with a pushing speed of 0.03 ml / min, an air flow pressure of 0.1 mpa, and a collection distance of 35 cm.
[0111] After replacing the solvent with acetonitrile, tetrahydrofuran, and DMF, spinning could not be carried out.
[0112] II. Effect tests
[0113] 1. Scanning electron microscopy test
[0114] Figure 1 The macroscopic morphology of the flexible ceramic block prepared in Example 1 is a flexible material with high resilience, such as Figure 2 the stress-strain curve (the stress-strain curve was obtained by using a uniaxial mechanical property testing machine, loading to the specified strain by displacement loading, and then outputting the strain value). In Example 1, it could recover at a strain of 40% - 70%. Observe the microscopic morphology of the connection structure through a scanning electron microscope, and the test results are as Figure 3 shown.
[0115] Figure 3 It can be observed that the flexible ceramic fiber sponge prepared in Example 1 is formed by fiber lap joints, and the diameters of the fibers are uniform and continuous.
[0116] The above results show that the ceramic fiber sponge prepared by the present invention is a flexible material and can be applied in more scenarios.
[0117] 2. Wave absorption performance test
[0118] The microwave absorption performance of Examples 1-2 and Comparative Examples 1-3 was tested on a vector network analyzer. The fibers were mixed with paraffin at a mass ratio of 1:9 and made into a circular ring through a mold. The complex permittivity (ε = ε' - jε”) and complex permeability (μ = μ' - jμ”) at 2-18 GHz were detected by the coaxial method using Agilent Technologies N5244A (since this material has no magnetism, the real and imaginary parts of the complex permeability are considered to be 0). Then, the minimum reflection loss value RL was calculated through a formula. The thicknesses of Examples 1-2 and Comparative Examples 1-3 were both 2.5 mm.
[0119]
[0120] d is the thickness of the coating, f is the frequency of the incident wave, c is the propagation rate of microwaves in a vacuum, r represents Examples 1-2 and Comparative Examples 1-3, and j is the imaginary unit.
[0121]
[0122] Table 1
[0123] <![CDATA[RL min (dB)]]> Example 1 -37.97 Example 2 -35.06 Comparative Example 1 -2.12 Comparative Example 2 -6.33 Comparative Example 3 -8.29
[0124] When RL min is less than -10 dB, it can absorb more than 90% of electromagnetic waves. Therefore, it can be seen from the data in Table 1 that the flexible ceramic fiber blocks prepared in Examples 1-2 of the present invention have excellent microwave absorption ability.
[0125] During the spinning process of Examples 1-2, there were no abnormal situations such as adhesion, and the spinning was smooth; the unsuitable spinning solutions of Comparative Examples 4-6 would cause the solution to be non-spinnable, unable to form fibers, and local stacking would occur, resulting in spinning failure.
[0126] In Comparative Example 1, the mass ratio of chloroform to DMF was changed. In Comparative Example 2, the mass ratio of PVP to polysilazane was changed. In Comparative Example 3, polysilazane was replaced by polycarbosilane. Although spinning was successful, its microwave absorption ability decreased significantly.
[0127] 3. Thermal insulation performance and porosity test
[0128] (1) The thermal insulation performance was tested by the hot plate method. Based on Fourier's law, a stable heat flow was established between the heating plate and the cooling plate, and the ceramic fiber was placed in the middle. The temperature difference and heat flux density on both sides of the material were measured to calculate the thermal conductivity (λ). The specific steps were as follows: Example 1 was cut into a cube with a side length of 1 cm 3 and installed between the hot plate (heating side) and the cold plate (cooling side). After reaching a steady state, the heat flow (Q, unit: W), temperature difference (ΔT, unit: K), and thickness (d, unit: m) were recorded, and λ = Q·d / (A·ΔT) was calculated (A is the area, unit: m2 ) Finally, the thermal conductivity (λ) of Example 1 was calculated to be 1.273 W / m·K, showing good heat insulation performance.
[0129] (2) Porosity test
[0130] Measure the dry weight: Place Example 1 on an electronic balance and measure its dry weight, denoted as m1.
[0131] Immerse in boiling water and cool: Completely immerse Example 1 in a beaker filled with distilled water, and perform the boiling operation until no bubbles adhere to the surface of the sample and no bubbles emerge from the water. Turn off the power and let it stand to cool.
[0132] Measure the suspended weight: Take out Example 1, quickly and gently wipe off the moisture on its surface with absorbent paper, and weigh it in a floating weight measuring instrument, denoted as m2.
[0133] Measure the wet weight: Take out Example 1, quickly wipe off the moisture on its surface with absorbent paper, and then place it on the electronic balance again to measure its wet weight, denoted as m3.
[0134] Calculate the porosity: According to Archimedes' principle, the volume of water displaced by the ceramic sample is the volume of the pores. By calculating the weight of the displaced water (i.e., the buoyancy), the volume of the pores can be deduced. Combining the dry weight, floating weight, and wet weight of the sample, the porosity can be calculated. The formula for porosity is:
[0135]
[0136] The amorphous SiCN ceramic fibers of the present invention increase the phonon scattering path and inhibit the heat transfer by lattice vibration. By constructing a porous structure (porosity > 70%) with SiCN ceramic fibers, gas conduction and convection can be reduced. Therefore, the thermal conductivity of Example 1 is low; at the same time, the present invention has good high-temperature stability (pyrolysis at 1400°C).
[0137] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than limiting the protection scope of the present invention. Any simple modification or equivalent replacement of the technical solution of the present invention by those of ordinary skill in the art does not depart from the essence and scope of the technical solution of the present invention.
Claims
1. A spinning solution, characterized in that, It includes a solvent and a precursor. The precursor is: polyvinylpyrrolidone and polysilazane; the solvent is chloroform and DMF.
2. The spinning solution according to claim 1, wherein, The solvent is chloroform and DMF with a mass ratio of 1:(1 - 4).
3. The spinning solution according to claim 1, characterized in that, The polyvinylpyrrolidone accounts for 7% - 15% of the mass of the spinning solution.
4. The spinning solution according to claim 1, characterized in that, The polysilazane accounts for 14% - 30% of the mass of the spinning solution.
5. The spinning solution according to any one of claims 1-4, characterized in that, By mass fraction, it includes 7% - 15% polyvinylpyrrolidone, 14% - 30% polysilazane and the balance of the solvent; and / or The mass ratio of the polyvinylpyrrolidone to the polysilazane is 1:(1 - 2).
6. A preparation method of a flexible ceramic fiber sponge, characterized in that, It includes the following steps: (1) Obtain a flexible fiber sponge by air - jet spinning the spinning solution according to any one of claims 1 - 5. (2) Dry - process the flexible fiber sponge obtained in step (1) to obtain a dried flexible fiber sponge. (3) Pyrolyze the dried flexible fiber sponge obtained in step (2) to obtain a flexible ceramic fiber sponge.
7. The preparation method according to claim 6, characterized in that, In step (1), the propulsion speed of the air - jet spinning is 0.01 - 0.03 ml / min, the collection distance is 20 - 35 cm, and the air pressure is 0.1 mpa - 0.2 mpa. The pyrolysis in step (3) is carried out under the protection of an inert gas. The temperature of the pyrolysis in step (3) is 1300 - 1500 °C.
8. A flexible ceramic fiber sponge prepared by the preparation method according to any one of claims 6 - 7.
9. The application of the flexible ceramic fiber sponge prepared by the preparation method according to any one of claims 6 - 7 in the integrated design of multifunctional materials; the multifunction is: wave absorption and heat insulation.
10. A thermal protection / absorbing wave device, characterized in that It includes a flexible ceramic fiber sponge prepared by the preparation method according to any one of claims 6 - 7.
Citation Information
Patent Citations
Preparation method of flexible hydrophobic silicon carbide nanofiber cloth with electromagnetic wave absorption effect
CN106757529A
Method for preparing spontaneous water-absorbing sponge for absorbing electromagnetic waves by utilizing high-speed airflow spinning
CN116623316A